Cord Blood IL-12 Confers Protection to Clinical Malaria in Early Childhood Life - Song, Y.; Aguilar, R.; Guo, J.; Manaca, M.; Nhabomba, A.; Berthoud, T.; Khoo, S.; Wiertsema, S.; Barbosa, A.; Quintó, L.; Laing, I.; Mayor, A.; et al. (Nature Publishing Group, 2018)
Using a well-designed longitudinal cohort, we aimed to identify cytokines that were protective against malaria and to explore how they were influenced by genetic and immunological factors. 349 Mozambican pregnant women and their newborn babies were recruited and followed up for malaria outcomes until 24 months of age. Six Th1 cytokines in cord blood were screened for correlation with malaria incidence, of which IL-12 was selected for further analyses. We genotyped IL-12 polymorphisms in children/mothers and evaluated the genotype-phenotype associations and genetic effects on IL-12 levels. Maternal IL-12 concentrations were also investigated in relation to Plasmodium infections and cord blood IL-12 levels. Our data showed that high background IL-12 levels were prospectively associated with a low incidence of clinical malaria, while IL-12 production after parasite stimulation had the opposite effect on malaria incidence. IL-12 genotypes (IL-12b rs2288831/rs17860508) and the haplotype CGTTAGAG distribution were related to malaria susceptibility and background IL-12 levels. Maternal genotypes also exhibited an evident impact on host genotype-phenotype associations. Finally, a positive correlation in background IL-12 levels between maternal and cord blood was identified. Thus, cord blood background IL-12 concentrations are important for protecting children from clinical malaria, likely mediated by both genotypes (children&mothers) and maternal immunity.